1993
DOI: 10.1073/pnas.90.8.3134
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to protect crop plants against viruses: pathogen-derived resistance blossoms.

Abstract: Since 1986, the ability to confer resistance against an otherwise devastating virus by introducing a single pathogen-derived or virus-targeted sequence into the DNA of a potential host plant has had a marked influence on much of the research effort, focus, and shortterm objectives of plant virologists throughout the world. The vast literature on coat protein-mediated protection, for example, attests to our fascination for unraveling fundamental molecular mechanism(s), our (vain) Despite extensive and sometim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
1
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(101 citation statements)
references
References 106 publications
1
97
1
2
Order By: Relevance
“…Pathogen-derived resistance (PDR) (Sanford & Johnston, 1985) against plant viruses has been demonstrated through genetic transformation of plants with genes that encode either wild-type or modified viral proteins (Fitchen & Beachy, 1993 ;Wilson, 1993). In many cases, the accumulation of transgenic viral proteins correlates with the level of resistance achieved, and protection has been proposed to involve protein interference with specific virus processes (Reimann-Philipp & Beachy, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogen-derived resistance (PDR) (Sanford & Johnston, 1985) against plant viruses has been demonstrated through genetic transformation of plants with genes that encode either wild-type or modified viral proteins (Fitchen & Beachy, 1993 ;Wilson, 1993). In many cases, the accumulation of transgenic viral proteins correlates with the level of resistance achieved, and protection has been proposed to involve protein interference with specific virus processes (Reimann-Philipp & Beachy, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Coat protein-mediated virus resistance has been successfully applied for a number of RNA plant viruses (Hull & Davies, 1992 ;Wilson, 1993). For the geminivirus tomato yellow leaf curl virus (TYLCV) Israel strain, Kunik et al (1994) observed a delay in the appearance of disease symptoms and subsequent recovery from symptoms in tomato plants expressing the TYLCV coat protein gene.…”
Section: Discussionmentioning
confidence: 99%
“…Coat protein-mediated resistance is, so far, the best studied method of protecting plants against virus infection (Hull & Davies, 1992 ;Wilson 1993). Two possible risks associated with viral coat proteinexpressing plants are conceivable : heterologous encapsidation and recombination.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, TMV in which the CP was replaced by the SHMV CP overcame CP-MR to the same extent as did SHMV. We conclude that CP-MR conferred by TMV CP involves interactions between amino acid sequences of the challenge viruses and the transgene protein other than those on the surface of the challenge virus.Coat protein-mediated resistance (CP-MR) has been widely used to develop protection in monocots and dicots against a number of different viruses (see reviews by Fitchen & Beachy, 1993;Wilson, 1993). However, the molecular and cellular nature of the resistance has not been fully elucidated for any example of CP-MR. We have focused our studies of CP-MR on protection against tobacco mosaic tobamovirus (TMV) in tomato and tobacco plants.…”
mentioning
confidence: 99%
“…Coat protein-mediated resistance (CP-MR) has been widely used to develop protection in monocots and dicots against a number of different viruses (see reviews by Fitchen & Beachy, 1993;Wilson, 1993). However, the molecular and cellular nature of the resistance has not been fully elucidated for any example of CP-MR. We have focused our studies of CP-MR on protection against tobacco mosaic tobamovirus (TMV) in tomato and tobacco plants.…”
mentioning
confidence: 99%